Pulmonary veno-occlusive disease: an uncommon cause of pulmonary hypertension. (1st February 2013) - Masters, Kyle; Bennett, Steven
Abstract : Pulmonary veno-occlusive disease (PVOD) is a rare and challenging cause of pulmonary hypertension. Clinical presentation is non-specific, including dyspnoea, cough and fatigue. Diagnosis of PVOD is typically based on high clinical suspicion with a definitive diagnosis confirmed by histology. Our case involves a healthy 21-year-old man who developed dyspnoea on exertion at an elevated altitude during deployment to Afghanistan. His work-up included an echocardiogram, a high-resolution CT scan, V/Q scan, pulmonary function tests with diffusion capacity, and a cardiac catheterisation with vasodilator challenge. Initially diagnosed with vasodilator responsive pulmonary arterial hypertension, an oral vasodilator was given with subsequent development of non-cardiogenic pulmonary oedema, thus confirming a clinical diagnosis of PVOD. He was medically stabilised with diuretic therapy, but developed progressive right-ventricular failure. For definitive treatment, he underwent a successful bilateral lung transplant. Explanted lung histology confirmed the diagnosis of PVOD.